Impact of the Covid-19 Pandemic on Anxiety Levels in Dental Clinic A.W. Sjahranie General Hospital Samarinda - Cristiani Nadya Pramasari; Nydia Hanan; Portuna Putra Kambaya; Ruslim, Andre Kusuma (Denta Journal Kedokteran Gigi, 2021)
Background: The Covid-19 is a viral infection caused by the novel coronavirus and interpersonal transmission occurs mainly via respiratory droplets and contact transmission. In some countries, the recommendations of the dental associations are to interrupt elective dental treatments, so only emergency or urgent cases are allowed. However, many patients are not aware of whether or not to attend their appointments at the dental clinic. Most of the patients are anxious but some patients feel calm to seek dental treatment. Purpose: This research is to find out the impact of the Covid-19 pandemic on anxiety levels and patient’s visit in Dental and Oral Clinic, A.W. Sjahranie General Hospital Samarinda. Materials and Method: This research was designed by the descriptive observational approach using a cross-sectional research design. The samples were new patients of child and adult who visited Dental and Oral Clinic, A.W. Sjahranie General Hospital Samarinda. The research was conducted through questionnaires to measure anxiety levels about Covid-19 pandemic conditions and the average anxiety level of patients associated with "stay at home" recommendation and their impact on dental care success. Result: The questionnaires were answered by 55 patients (23 male/42% and 32 female/58%) who visited the Dental and Oral Clinic, A.W. Sjahranie General Hospital Samarinda. The average level of patient anxiety for Covid-19 pandemic conditions is 4.87 for male patients and 4.42 for female patients. The level of anxiety about the impact of the Covid-19 pandemic on dental care is about the same in both men and women. Conclusion: Male patients are more anxious than women about the Covid-19 pandemic. But both showed similar anxiety about how pandemic conditions could affect their dental care.